Apostles of Disunion - Serrano, Jonathan (The Toro Historical Review, 2021)
This paper analyzes the rhetoric of appointed state-commissioners from the Southern States advocating for secession prior to the American Civil War. The rhetoric used is very similar across all state-appointed commissioners as much of it was based on racial claims in which their biases, racism, and fear energized their claims for the need for secession. This paper explores the topic of succession exclusively through a Southern lens as the justification of succession is based on the Southern belief that all state's rights had been violated without giving slavery being the cause any validation.